2020
DOI: 10.7454/uiphm.v4i1.242
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nurses’ Knowledge of Initial Assessment and Application of Early Warning System At Emergency Department of Type A Hospital In Jakarta

Abstract: <div class="WordSection1"><p class="AbstractContent"><strong>Objective:</strong> Early warning system (EWS) is a physiological scoring to observe the patient’s condition not only in hospital wards but also in Emergency Department (ED). At an overcrowded ER that have slow of patient flow, EWS is use as an early detection of patient’s deterioration by observing the vital signs. The purpose of this study was to identify the relationship between nurses’ knowledge of initial assessment and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Penelitian yang dilakukan oleh Purnamasari dan Aryani (2020) menemukan bahwa semakin tinggi tingkat pengetahuan perawat maka perilaku semakin meningkat. Hal ini juga harus diikuti oleh pelatihan secara berkala sehingga dapat mempertahankan penggunaan EWS yang baik (Purnamasari & Aryani, 2020). Pada konteks pelaksanaan tugas keperawatan, pengetahuan merupakan suatu domain yang sangat penting untuk pembinaan perilaku, karena perilaku yang didasarkan pengetahuan akan lebih bertahan lama dibandingkan dengan perilaku yang tidak berdasarkan pengetahuan.…”
Section: Pembahasanunclassified
“…Penelitian yang dilakukan oleh Purnamasari dan Aryani (2020) menemukan bahwa semakin tinggi tingkat pengetahuan perawat maka perilaku semakin meningkat. Hal ini juga harus diikuti oleh pelatihan secara berkala sehingga dapat mempertahankan penggunaan EWS yang baik (Purnamasari & Aryani, 2020). Pada konteks pelaksanaan tugas keperawatan, pengetahuan merupakan suatu domain yang sangat penting untuk pembinaan perilaku, karena perilaku yang didasarkan pengetahuan akan lebih bertahan lama dibandingkan dengan perilaku yang tidak berdasarkan pengetahuan.…”
Section: Pembahasanunclassified
“…It was reported that the decision-making and professional abilities of nurses might be influenced by the learning experiences they have on the job. It is assumed that the nurse with the highest level of training, education, and expertise will be proficient in the nursing profession [22].…”
Section: Relationship Between Nurse's Knowledge and Initial Assessmentmentioning
confidence: 99%